EFEKTIVITAS PENDEKATAN CULTURALLY RESPONSIVE TEACHING TERHADAP HASIL BELAJAR SISWA KELAS V SDN DUKUH KUPANG V - Mohammad Maulana Zein Akbar; Fatkul Anam; Siti Juwariyah (JIP: Jurnal Ilmu Pendidikan, 2025)
The low ability of students to understand the concept of presenting data in the form of bar charts is a problem that is often found in elementary schools. This study aims to analyse the effectiveness of the Culturally Responsive Teaching (CRT) approach in improving the learning outcomes of grade V students on the presentation of data in the form of bar charts. The research method used is classroom action research (PTK) with a design that includes four stages: planning, implementation, observation, and reflection. The research subjects were grade V students with a total of 28 students. Data collection was conducted through learning outcome tests, student activity observations, and documentation. The results showed a significant increase in students' ability to understand the concept of presenting data with bar charts after the implementation of the CRT approach. In the pre-cycle stage, the completeness of learning outcomes only reached 46%. After the implementation of CRT, in cycle I, the learning completeness was 75%, and in cycle II it reached 89%. The Culturally Responsive Teaching (CRT) approach proved to be effective in improving student learning outcomes because it had reached the predetermined indicators, namely more than 75% of student scores reached the KKM score or >75%.